When the Law Advances Access to Learning: Locke and the Origins of Modern Copyright - Willinsky, John (KULA)

(untitled) (University of Victoria Libraries, 2017)
In light of the challenge and promise currently facing scholarly publishing’s move to digital models of greater openness, this paper offers a point of historical reflection on an earlier era of concern over sustainable access to learned works. It reports on a period of great turmoil in publishing that ran from the end of British book licensing in 1695, which unleashed a great wave of print piracy and sedition, to the legal remedy afforded by the Statute of Anne 1710, which introduced what we now think of as modern copyright law. The paper begins with John Locke’s lobbying of Parliament to end the effrontery of press censorship and monopoly maintained by the three-decade old Licensing Act of 1662. The scholar-friendly legal reforms of this act that Locke proposed in the 1690s were not taken up by Parliament when it allowed the act to expire in 1695. However, six years after Locke’s death in 1704, his and others’ proposed reforms were to find a place in the Statute of Anne 1710. This legislation was the first to vest authors with an exclusive, limited-term right to print copies of their work, while also protecting the access rights of scholars and the public to these and other works. I argue that the history of the statute reveals how the age of copyright began with striking a fine legislative balance between the interests of learning and those of commercial publishing, while also offering further insight into Locke’s influential work on property rights and limits. My hope is that this portrayal of Locke’s relatively effective political intervention as scholar-activist and public defender of learning in relation to the subsequent Statute of Anne might inspire and lend weight to the academic community’s current grappling with the growing commercial dominance of scholarly publishing.